A Comprehensive Numerical Study on Building-Excavation Interaction - Arman Maddah; Abbas Soroush (Salehan Institute of Higher Education, 2020)
This paper presents results of a plane strain comprehensive numerical study on the interaction between a 31-meter-deep excavation and an adjacent 12-story building; the study emphasizes on parametric analyses with respect to the building characteristics, such as the building width in plan (B), i.e., the side perpendicular to the excavation wall, the embedment depth of the building foundation (D), as well as the building distance to the excavation edge (e). Through the parametric analyses and assuming different values for B, D, and e, settlements and rotations of the building and horizontal displacements of the excavation edge were computed and evaluated using the finite element method adopted in PLAXIS 3D software. Prior to the parametric study, the numerical modeling was verified by modeling a recorded case study, which is an anchored deep excavation adjacent to a 12-story building. The results of the parametric analyses suggest that for the given soil and excavation, (1) the position of the developing potential failure surface, PFS, in the soil behind the excavation is almost independent from the building location and (2) the position of the building with respect to the outcrop of the PFS in the excavation crest, i.e., if the building locates fully on the potential failure wedge or PFS intersect the building base, is the main factor affecting the induced displacements and rotations of the building.